2018
DOI: 10.2298/tsci170626056z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effects of light intensity on energy conversion efficiency of photo-thermo chemical synergetic catalytic water splitting

Abstract: Hydrogen production from water using a catalyst and solar energy was an ideal future fuel source. In this study, an elaborate experimental test rig of hydrogen production from solar water splitting was designed and established with selfcontrolled temperature system. The effects of light intensity on the reaction rate of hydrogen production from solar water splitting were experimentally investigated with the consideration of optical losses, reaction temperature, and photocatalysts powder cluster. Besides, a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Many research groups have already studied the influence of lamp intensity on photocatalytic efficiency ( Pansamut et al, 2013 ; Kumar and Pandey, 2017 ; Wang et al, 2020 ; Amakiri et al, 2021 ). In most cases, the authors reported that hydrogen production increased with the increasing intensity of irradiation used ( Baniasadi et al, 2013 ; Bell et al, 2013 ; Cheng et al, 2018 ). However, higher light intensities can cause much more significant energy losses instead of favoring the degradation of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have already studied the influence of lamp intensity on photocatalytic efficiency ( Pansamut et al, 2013 ; Kumar and Pandey, 2017 ; Wang et al, 2020 ; Amakiri et al, 2021 ). In most cases, the authors reported that hydrogen production increased with the increasing intensity of irradiation used ( Baniasadi et al, 2013 ; Bell et al, 2013 ; Cheng et al, 2018 ). However, higher light intensities can cause much more significant energy losses instead of favoring the degradation of organic compounds.…”
Section: Introductionmentioning
confidence: 99%